THE EFFECTS OF TARAXACUM OFFICINALE EXTRACTS (TOE) SUPPLEMENTATION ON PHYSICAL FATIGUE IN MICE - Jinchun, Z.; Jie, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The study is to investigate the effectof Taraxacum officinale extracts (TOE) supplementation on physical fatigue based on the forced swimming capacity in mice. Forty Kunming male mice were randomly divided into 4 groups, i.e., normal control (NC) and three doses of TOE treated group (High-dose, Middle-dose and Low-dose). Three TOE treated groups were treated by oral TOE with 10, 30 and 100mg/kg b.w respectively for a period of 42 days. The normal control group was given a corresponding volume of sterile distilled water. After 6 weeks, the forced swimming capacity and blood biochemical parameters in mice were measured, and the result showed that TOE had an anti- physical fatigue effect. It enhanced the maximum swimming capacity of mice, effectively delayed the lowering of glucose in the blood, and prevented the increase in lactate and triglyceride concentrations.